Associations Between Parental Depression, Self-efficacy, and Early Childhood Development in Malnourished Haitian Children - Xinshu She MD, MPH; Sajithya Perera MD; Martine Andre MD; Jacklin St. Fleur MD; Johanne Hilaire MD; Andrea Evans MD, MSc; Jack Long MD; Delight Wing MD; Christopher Carpenter MD, MPH; Kim Wilson MD, MPH; Judith Palfrey MD; Sara Stulac MD, MPH (SAGE Publishing, 2022)
Background . Haiti lacks early childhood development data and guidelines in malnourished populations. Literature shows that developmental interventions are crucial for improving developmental outcomes malnourished children. This study examines the prevalence of early childhood development delays in a cohort of malnourished Haitian children and their associations with parental depression and self-efficacy. Methods . We used cross-sectional data from 42 patients 6 months to 2 years old in Saint-Marc, Haiti. We assessed their developmental status using the Ages and Stages Questionnaire. Parents were surveyed on depression symptoms and self-efficacy using validated surveys developed for low-resource settings. Demographic and socio-economic data were included. Prevalence of early childhood development delays and high parental depression risk were calculated. Multivariable logistic regression analyses were used to test whether parental depression risk and low self-efficacy were associated with a higher risk for childhood developmental delays. Results . Among participants, 45.2% (SD = 7.7%) of children with a recorded ASQ met age-specific cutoffs for developmental delay in one or more domains. 64.3% (SD = 7.4%) of parents were at high risk for depression. 47.6% (SD = 7.7%) of parents reported relatively low self-efficacy. Multivariable analysis showed that low parental self-efficacy was strongly associated with developmental delays (OR 17.5, CI 1.1-270.0) after adjusting for socioeconomic factors. Parental risk for depression was associated with higher odds (OR 4.6, CI 0.4-50.6) of children having developmental delays but did not reach statistical significance in this study. Conclusion . Parental self-efficacy was protectively associated with early childhood developmental delays in malnourished Haitian children. More research is needed to design contextually appropriate interventions.